Propriedades térmicas, dielétricas e vibracionais de Ormosil's baseados em DPMS e TEOS dopados com MDS - Pinto, Raffael Costa de Figueiredo (2008)
In this work have been investigated the dielectric and vibrational properties of the ORMOSIL membranes based on PDMS and TEOS doped with MDS using the Di erential Scanning Calorimetry (DSC), impedance, Raman and infrareds spectroscopy technics. Such membranes are hybrid organic-inorganic materials with potential application in PEMFC (Proton Exchange Membrane Fuel Cell) and were doped with concentrations 0%(Pure Membrane), 5%, 10%, 20% e 30% of MDS. The thermal measurements were performed in the range from room temperature and 550 oC. The results showed that, after the MDS inclusion, the membranes absorb water. Besides, then thermal stability of the membranes decreased with the MDS inclusion. The dielectrics measurements were performed in temperature range of 313K-373K. The results showed that room temperature conductivity increases linearly with the frequency, until 353K, suggesting a hopping conduction and leaving this linear behavior above 353K. Besides, it was observed that conductivity doesn't increases linearly with MDS concentration, but increases until maximal value for 20% MDS concentration and decreases again for 30% MDS concentration de ning a synergetic e ect, which probably is associate with con gurational arrange of microcristallites MDS. Another feature of that membranes is a relaxation process visible in the electrical module graphics which appear just in doped membranes, being however, due to the MDS. The vibrational properties of hybrids membranes were obtained through Raman scattering and infrared. The results con rmed the presence of Si¡O¡Si, Si¡C, Si¡OH, C2H5, Si¡CH3, CH3, CH2, C¡H, S=O and S¡O groups. Where the S=O and S¡O groups are presents just in MDS compound. Consequently, their respective peaks appear only in the doped membrane spectra.